2020
DOI: 10.7759/cureus.11637
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Trauma Theatre Efficiency

Abstract: Introduction A large transformation in the management of trauma has ensued following the COVID-19 (coronavirus disease 2019) pandemic. There has been an increase in reliance on guidance for decision-making and alterations in the working of the trauma theatre. This has largely been due to the safety measures implemented. Theatre efficiency has gained increasing importance over the years, and with the added pressure of the pandemic, it is essential that trauma theatres operate efficiently. There has been no data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 10 publications
0
12
5
Order By: Relevance
“…Khadabadi et al . [ 22 ] and Cuerva et al . [ 23 ] have also reported an increase in operative and anaesthetic time during the COVID-19 pandemic for trauma surgeries and caesarean sections, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Khadabadi et al . [ 22 ] and Cuerva et al . [ 23 ] have also reported an increase in operative and anaesthetic time during the COVID-19 pandemic for trauma surgeries and caesarean sections, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supported by the data from available studies. Khadabadi et al 4 evaluated 45 full-day lists in 2019 and 50 full-day lists in 2020 during April and May. They found that operative time and anaesthetic time went up significantly in 2020 in comparison to 2019.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is supported by the literature, with suggestions that early in the UK pandemic in March 2020, outcomes were worse, using theatre efficiency as an example. 28 However, with the progression of the pandemic, theatre efficiency improved. 29 This can be explained locally due to administrative disruptions, such as re-deployment of staff to intensive care, a lack of understanding on the management of COVID-19, and the lack of personal protective equipment.…”
Section: Discussionmentioning
confidence: 99%